The effect of warmth acclimation on behaviour, thermophysiology and perception. Issue 7 (3rd October 2017) - Pallubinsky, Hannah; Kingma, Boris R. M.; Schellen, Lisje; Dautzenberg, Bas; van Baak, Marleen A.; van Marken Lichtenbelt, Wouter D.
ABSTRACT: Public and commercial buildings tend to overheat and considerable energy is consumed by air-conditioning and ventilation. However, many occupants remain unsatisfied and consequently exhibit thermoregulatory behaviour (TRB), e.g. opening windows or controlling the air-conditioning. This, in turn, might negatively influence the building energy use. This paper hypothesizes that warmth acclimation influences thermophysiology, perception and TRB in a warm environment. Therefore, the effect of warmth acclimation on TRB, physiology and perception is investigated. Twelve participants underwent a so-called SWITCH protocol before and after warmth acclimation (7 days, 6 h/day, about 33°C, about 22% RH). During SWITCH, the participants chose between a warm (37°C) and a cold (17°C) condition. TRB was determined by the number of switches and the time spent in a specific condition. Mean skin temperature was recorded to assess behavioural thresholds. Thermal comfort and sensation were indicated on visual analogue scales (VAS). After acclimation, the upper critical behavioural threshold significantly increased from 35.2 ± 0.6 to 35.5 ± 0.5°C ( p  ≤ 0.05) and the range of mean skin temperatures at which no behaviour occurred significantly widened (3.6 ± 0.7 to 4.2 ± 0.6; p  < 0.05). The total number of switches tended to decrease ( p  = 0.075). The present study is the first to show that prolonged passive exposure to warmth extends TRB thresholds.